2005
DOI: 10.1164/rccm.200409-1168oc
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Analysis and Aberrant Expression of the MUC5B Gene in Diffuse Panbronchiolitis

Abstract: Diffuse panbronchiolitis (DPB) is a chronic inflammatory airway disease predominantly affecting Asian populations. DPB is considered to be a complex genetic disease. Considering the mucous hypersecretion of the disease, we hypothesized that the transcriptional activity of mucin genes may be altered in DPB. We analyzed nucleotide sequences of regulatory region of six mucin genes--MUC1, MUC2, MUC4, MUC5AC, MUC5B, and MUC7--and detected their promoter polymorphisms. Among them, the insertion/deletion polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 40 publications
3
56
0
1
Order By: Relevance
“…Other variants in the promoter of MUC5B have been reported to be associated with panbronchiolitis in a Japanese population, providing support for this further investigation of MUC5B among Asian populations. 17 Future studies will determine exactly which variants are driving the observed associations and their potential role in the mechanism of disease. Th ese results suggest that these populations and other racial/ethnic populations will need to be studied individually to verify these fi ndings and identify the full range of genetic components that account for IPF risk.…”
Section: Discussionmentioning
confidence: 99%
“…Other variants in the promoter of MUC5B have been reported to be associated with panbronchiolitis in a Japanese population, providing support for this further investigation of MUC5B among Asian populations. 17 Future studies will determine exactly which variants are driving the observed associations and their potential role in the mechanism of disease. Th ese results suggest that these populations and other racial/ethnic populations will need to be studied individually to verify these fi ndings and identify the full range of genetic components that account for IPF risk.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data show a difference in LD between pairs of these markers in the cases and controls, and ongoing work includes searching for, and validating, suitably informative MUC5AC SNPs to test in this cohort, as well as study of the longitudinal '1946' cohort (Rousseau et al 2006). The observation of 10/70 chromosomes with an identical haplotype extending from MUC2 to MUC5B, and evidence of functional variation in the MUC5B promoter (Kamio et al 2005), means that it will also be worth testing MUC5B in these and other asthma cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory infiltrate is composed of neutrophils, CD8 T-lymphocytes and foamy macrophages. The airway epithelium may be damaged and shows extensive goblet cell hyperplasia with secretion of MUC5AC and MUC5B mucins [174,175]. Genetic predisposition related to specific HLA genotypes or polymorphisms in MUC5B mucin have been suggested [176].…”
Section: Diffuse Panbronchiolitismentioning
confidence: 99%